Plant and pathogen nutrient acquisition strategies - Fatima, Urooj; Senthil-Kumar, Muthappa (Frontiers in Plant Science, 2015)
Nutrients are indispensable elements required for the growth of all living organisms including plants and pathogens. Phyllosphere, rhizosphere, apoplast, phloem, xylem and cell organelles are the nutrient niches in plants that are the target of bacterial pathogens. Depending upon nutrients availability, the pathogen adapts various acquisition strategies and inhabits the specific niche. In this review, we discuss the nutrient composition of different niches in plants, the mechanisms involved in the recognition of nutrient niche and the sophisticated strategies used by the bacterial pathogens for acquiring nutrients. We provide insight into various nutrient acquisition strategies used by necrotrophic, biotrophic and hemi-biotrophic bacteria. Specifically we discuss both modulation of bacterial machinery and manipulation of host machinery. In addition, we highlight the current status of our understanding about the nutrient acquisition strategies used by bacterial pathogens, namely targeting the sugar transporters that are dedicated for the plant’s growth and development. Bacterial strategies for altering the plant cell membrane permeability to enhance the release of nutrients are also enumerated along with in-depth analysis of molecular mechanisms behind these strategies. The information presented in this review will be useful to understand the plant-pathogen interaction in nutrient perspective.